(untitled) (Scientific Journal of Educational Management, Research and law, 2025)
This study examined the challenges and prospects of implementing digital forms and records in the administration of public secondary schools in Rivers State. The study reviewed the various types of digital forms and records used by school administrators to elicit information from students, teachers, and parents/guardians. The forms include electronic application, registration, consent, survey, incident, scholarship and financial aid, and parents/teachers invite. In addition, the records were categorized into electronic statutory and non-statutory basis. In spite of the advantage of integrating digital forms and records, the study observed that some principals in public secondary school in Rivers State seems to be relying heavily on the traditional method of paperwork in carrying out eminent administrative duties despite the awareness of computer assisted methodology. Judging from the UNESCO, the study described digital forms and records system as an organized classification and filing of the school archives in a way that makes it easy to search, access, retrieve and use the data information for school functionality. The study accounted that, the absence of power supply, digital facilities, Poor knowledge of ICT, resistance to change, Management of database, paucity of fund, technical support and maintenance are some of the challenge impeding the implementation of digital forms and records by school administrators. Irrespective of these foreseen challenges, the study upholds that implementing digital forms and records has the prospects of; promoting work efficiency, cutting cost, speedy accessibility to database, modernize effective communication. However, the study suggested among others that Rivers State Ministry of Education, and Private donors whose activities are domiciled in the state should see the need for regular power supply across schools, procure digital facilities, provide grant, sensitize school members on how to use of emerging technologies.